Bi-monthly hepatic arterial infusion chemotherapy as a novel strategy for advanced hepatocellular carcinoma in decompensated cirrhotic patients - Kei Moriya; Tadashi Namisaki; Shinya Sato; Masanori Furukawa; Akitoshi Douhara; Hideto Kawaratani; Kosuke Kaji; Naotaka Shimozato; Yasuhiko Sawada; Soichiro Saikawa; Hiroaki Takaya; Koh Kitagawa; et al. (Clinical and Molecular Hepatology, 2019)
Background and Aims We previously reported the comparable efficacy of bi-monthly hepatic arterial infusion chemotherapy (B-HAIC) to that of sorafenib chemotherapy for the treatment of advanced hepatocellular carcinoma (aHCC) in patients with compensated cirrhosis. In this study, we demonstrate the efficacy of B-HAIC in patients with decompensated cirrhosis. Methods Forty-five patients with aHCC refractory to transcatheter arterial chemo-embolization (TACE) were treated with B-HAIC and were divided into two groups according to hepatic functional reserve (Child-Pugh grade). Overall survival period, treatment response, and adverse events in each group were analyzed. Results Efficacy and disease control rates in the Child-Pugh B group (n=24; 21% and 71%, respectively) were not significantly impaired compared the Child-Pugh A group (n=21; 38% and 67%, respectively). Median survival time and survival rate at 12 months in the Child-Pugh B group were 422 days and 58.3%, respectively, whereas those in the Child-Pugh A group were 567 days and 70.8%, respectively. Importantly, the hepatic functional reserve of patients did not worsen in either group during the treatment period. Furthermore, the occurrence rate of adverse events leading to discontinuation of anti-tumor treatment was not significantly increased in the Child-Pugh B group. Conclusions Given the preservation of hepatic functional reserve afforded by B-HAIC chemotherapy in patients with decompensated cirrhosis, B-HAIC might be an acceptable alternative strategy for aHCC patients who do not respond to TACE.